PROBLEMS OF CREATION CRIME THROUGH THE USE OF DEMOCRATIC DATABASE SYSTEMS IN E-ID - Lukitasari, Diana (Universitas Negeri Semarang (UNNES), 2017)
This study aims to analyze the policy of crime prevention based on population database system in E-ID program. This research uses normative research method use legislation and conceptual approach. The legal materials use primary and secondary legal materials which analyzed deductively. The result of the study explains that the E-ID database system that contains the complete information of a citizen, including the criminal record should be a reference in the prevention of crime that has been done. The policy model is to integrate the e-ID card program as an integrated population administration system with police agencies, prosecutors, and especially prisons. Law enforcers will easily get information related to each person's resident document. The document will also include a track record of someone who is constantly updated at all times who will help the community to monitor the actor of crimes.